THERE IS NO POSSIBILITY OF ANOTHER SUBJECT ON THE PERSONA “WE” FROM REAGAN’S POEM LIFE - Astrinda Nilasastri Iswalono (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
Written by young Reagan, Life is a poem with a distinctive discourse as a literary work in the beginning of American modernism. The study of Life in the present article focuses on the interpretation of “we” and is contextualized within the historical narratives of the Puritans and the spirit of American Dream in the 20s. The analysis of the poem’s representations of the symbolic, the imaginary, and the Truth presented here is a Žižekian reading of the subjects “we” in the poem’s text who appear to get themselves into a pseudo activity in relation to the narratives of the Founding Fathers as the chosen ones in the holy journey of establishing America. The speaker of the poem, which is part of “we,” reflects the spirit of American Dream and reminds his fellow Americans to keep going amidst the feeling of alienation caused by the modern capitalism that is expressed by words “suffer”, “struggle”, “weep”, “drench”, “break”, “jade”, “sorrow”, “warp” and “pain” 15 times in only 8 stanzas/32 lines. The speaker’s sense of Americanism becomes the only Truth for the “we” until they grow their own Cynical Awareness.